2016
DOI: 10.3390/biom6020017
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Acetaldehyde in Ethanol-Induced Cell Cycle Impairment

Abstract: Background: Hepatocytes metabolize the vast majority of ingested ethanol. This metabolic activity results in hepatic toxicity and impairs the ability of hepatocytes to replicate. Previous work by our group has shown that ethanol metabolism results in a G2/M cell cycle arrest. The intent of these studies was to discern the roles of acetaldehyde and reactive oxygen, two of the major by-products of ethanol metabolism, in the G2/M cell cycle arrest. Methods: To investigate the role of ethanol metabolites in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In this regard, few data regarding the effects of alcohol on hepatocytes’ cell cycle and proliferation are available, and remain quite controversial. Classical in vitro studies performed by Clemens and co-workers [ 109 ] indicated that alcohol promotes cell cycle arrest of hepatocytes in G2/M phase and senescence via increased accumulation of the phosphorylated inactive form of the cyclin-dependent kinase, p-Cdk2, and of the cyclin dependent kinase inhibitor, p21. The augmented levels of these proteins result in a direct effect of acetaldehyde, rather than a consequence of oxidative stress.…”
Section: Alcohol and The Cell Cycle Machinery: Hepatocyte Cell Deamentioning
confidence: 99%
“…In this regard, few data regarding the effects of alcohol on hepatocytes’ cell cycle and proliferation are available, and remain quite controversial. Classical in vitro studies performed by Clemens and co-workers [ 109 ] indicated that alcohol promotes cell cycle arrest of hepatocytes in G2/M phase and senescence via increased accumulation of the phosphorylated inactive form of the cyclin-dependent kinase, p-Cdk2, and of the cyclin dependent kinase inhibitor, p21. The augmented levels of these proteins result in a direct effect of acetaldehyde, rather than a consequence of oxidative stress.…”
Section: Alcohol and The Cell Cycle Machinery: Hepatocyte Cell Deamentioning
confidence: 99%
“…The results showed that [4]helicenium significantly activated P53 and P21 in SK‐Hep1, but had no effect on HL7702 (Figure f). In addition, p‐CDC2, an important regulator in promoting G2/M phase transition, was inhibited in SK‐Hep1 after the treatment of [4]helicenium (Figure f), further implying that [4]helicenium‐treated HCC cell confronted with a problem of cell cycle progression defects. It appeared that the selective inhibition of HCC cell growth by [4]helicenium is mainly due to cell cycle arrest and cell apoptosis increment.…”
Section: Resultsmentioning
confidence: 96%
“…AcAld also causes mtDNA damage, and mtDNA deletions occur in >60% of patients with alcoholic steatosis (Fromenty, et al, 1995). Progressive loss of hepatocytes signifies a failure of hepatocellular regeneration, which is otherwise extraordinary in liver, an effect that may be due to AcAld-mediated G2/M cell cycle arrest (Diehl, 2005;Scheer, et al, 2016). Compromised bioenergetics in hepatocytes with mtDepo may also contribute to failure of regeneration.…”
Section: Relation Of Ethanol-induced Mitochondrial Alterations To Patmentioning
confidence: 99%